2020
DOI: 10.1002/solr.202000291
|View full text |Cite
|
Sign up to set email alerts
|

Thick‐Film Low Driving‐Force Indoor Light Harvesters

Abstract: Organic indoor photovoltaic (IPV) devices have tremendous potential for the wireless charging of internet of things (IoTs). [1-6] An ideal bulk heterojunction (BHJ) adopted for indoor light harvesters should satisfy both the requirements of device performance and fabrication feasibility. [7-12] The power conversion efficiency (PCE) of IPV cells can be optimized by adjusting donor:acceptor (D:A) materials and weight fractions for the spectral matching with the indoor light sources (e.g., fluorescence, light-emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Polymers with a 5,6-difluorobenzothiadiazole (ffBT) unit have experienced a long period of development in the thick-film OPV research field. [47][48][49][50][51][52][53][54] A representative class of polymer donor with thickness-insensitive characteristics is that of containing ffBT and tetrathiophene, namely FBT-Th 4 (1,4), with chemical structure shown in Figure 5A. The OPV device based on this copolymer as donor and PC 71 BM F I G U R E 5 (A) Chemical structure of part of ffBT-based polymers.…”
Section: 6-difluorobenzothiadiazole-based Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers with a 5,6-difluorobenzothiadiazole (ffBT) unit have experienced a long period of development in the thick-film OPV research field. [47][48][49][50][51][52][53][54] A representative class of polymer donor with thickness-insensitive characteristics is that of containing ffBT and tetrathiophene, namely FBT-Th 4 (1,4), with chemical structure shown in Figure 5A. The OPV device based on this copolymer as donor and PC 71 BM F I G U R E 5 (A) Chemical structure of part of ffBT-based polymers.…”
Section: 6-difluorobenzothiadiazole-based Polymersmentioning
confidence: 99%
“…Polymers with a 5,6‐difluorobenzothiadiazole (ffBT) unit have experienced a long period of development in the thick‐film OPV research field 47–54 . A representative class of polymer donor with thickness‐insensitive characteristics is that of containing ffBT and tetrathiophene, namely FBT‐Th 4 (1,4), with chemical structure shown in Figure 5A.…”
Section: Molecular Design Strategies For Thickness‐insensitive Materialsmentioning
confidence: 99%
“…First, the calculation was carried out for a wide set of data from literature [16][17][18][19][30][31][32][33][34][35] for the whole set of different LEDs presented above with a constant illuminance of 200 lux. Unfortunately, some high-performance solar cells could not be included due to lack of necessary data.…”
Section: Comparing Efficiencies Of Different Publicationsmentioning
confidence: 99%
“…More importantly, the shunt resistance ( R p ) was increased by one order of magnitude due to the modification of PEIE, the large R p is associated with the performance maximization in indoor OSCs. [ 57‐60 ] In addition, Lee et al found a more simple one‐step method to fabricate the self‐assembled bilayer with PEI bottom layer and photoactive top layer. [ 61 ] During the spin‐coating process of PEI‐mixed BHJ active layer (PEI:BHJ), PEI could uniformly distribute at the bottom of the active layer and thereby influence the WF of ITO.…”
Section: The Progress In I‐oscsmentioning
confidence: 99%
“…More importantly, the shunt resistance (R p ) was increased by one order of magnitude due to the modification of PEIE, the large R p is associated with the performance maximization in indoor OSCs. [57][58][59][60] In addition, Lee et al found a more simple one-step method to fabricate the Table 2. WF of conducting materials modified with/without insulating polymer, as independently measured by Kelvin probe in air and by UPS.…”
Section: Insulating Polymer-modified Electrodementioning
confidence: 99%